2009
DOI: 10.1063/1.3247833
|View full text |Cite
|
Sign up to set email alerts
|

Exact ground state Monte Carlo method for Bosons without importance sampling

Abstract: Generally "exact" Quantum Monte Carlo computations for the ground state of many Bosons make use of importance sampling. The importance sampling is based, either on a guiding function or on an initial variational wave function. Here we investigate the need of importance sampling in the case of Path Integral Ground State (PIGS) Monte Carlo. PIGS is based on a discrete imaginary time evolution of an initial wave function with a non zero overlap with the ground state, that gives rise to a discrete path which is sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 34 publications
(76 reference statements)
4
92
0
Order By: Relevance
“…II.B.1). Recent applications of the PIGS method involving high-order decomposition methods have shown that it is actually possible to obtain results that are completely independent of the trial wave function that is used as boundary condition (Rossi et al, 2009;Rota et al, 2010). Even in the limiting case of considering only the symmetry requirement of the system (e. g., ψ(R) = 1 in the bosonic case) the PIGS method works reliably, with the only penalty of producing slightly larger variances.…”
Section: Path-integral Ground-state Monte Carlomentioning
confidence: 99%
“…II.B.1). Recent applications of the PIGS method involving high-order decomposition methods have shown that it is actually possible to obtain results that are completely independent of the trial wave function that is used as boundary condition (Rossi et al, 2009;Rota et al, 2010). Even in the limiting case of considering only the symmetry requirement of the system (e. g., ψ(R) = 1 in the bosonic case) the PIGS method works reliably, with the only penalty of producing slightly larger variances.…”
Section: Path-integral Ground-state Monte Carlomentioning
confidence: 99%
“…To access static structural properties of the nonequilibrium pH 2 -oD 2 quantum liquid mixtures we have carried out path-integral Monte Carlo (PIMC) simulations [29] by using a canonical [30] Worm algorithm [31]. We have simulated mixtures of up to 300 molecules in boxes with periodic boundary conditions with 0, 3, and 10% oD 2 at T = 13 K, with 50% oD 2 at T = 14.5 K, and with 90, 97, and 100% oD 2 at T = 17 K. In order to avoid the crystallization of the mixtures we followed the strategy reported in Ref.…”
mentioning
confidence: 99%
“…The PIGS method provides estimates of ground-state properties and imaginary-time correlations functions, which are only affected by two errors: (i) the use of a finite imaginary time of projection in (8), and (ii) the use of a finite time step in (9). The biases introduced by these approximations can be reduced below the statistical uncertainties of the calculation by taking τ sufficiently large and δτ sufficiently small [43]. For the small imaginary-time propagator we have used the pair-product approximation [4] with imaginary time step δτ = 120ǫ −1 at ρ * = 0.01, δτ = 60ǫ −1 at ρ * = 0.0175 and δτ = 30ǫ −1 at ρ * = 0.0225; total imaginary projection time, τ , ranges from 2400 ǫ −1 to 4800 ǫ −1 depending on the density.…”
Section: The Pigs Methodsmentioning
confidence: 99%
“…The quality of the trial wavefunction, however, has a determining impact on the efficiency and accuracy of the calculation [43]. Shadow wavefunctions [19,[32][33][34][35] (SWFs) take into account interparticle correlations by introducing auxiliary variables S = (s 1 .…”
Section: Shadow Trial Wavefunctions and The Shadow-pigs Methodsmentioning
confidence: 99%